Evaluation of a Community-Based Exercise Program for Breast Cancer Patients Undergoing Treatment. Issue 6 (November 2015) - Leach, Heather J.; Danyluk, Jessica M.; Nishimura, Kathryn C.; Culos-Reed, S. Nicole
Abstract : Background: Exercise is important during treatment for breast cancer to alleviate the usual declines in physical and emotional health and overall health-related quality of life (HRQL). Objective: This study evaluated the effectiveness, safety, and enjoyment of a community exercise program for breast cancer patients who were currently undergoing or within 3 months of completing chemotherapy or radiation treatment. Methods: B reast cancer patients E ngaging in A ctivity while U ndergoing T reatment (BEAUTY) is a 12-week program of resistance, aerobic, and flexibility exercise. Participants completed pre and post fitness assessments, and questionnaires to measure HRQL, fatigue, cognitive function, and depressive symptoms. Participants had access to group exercise classes and were provided a home-based exercise program. Results: Participants (n = 80) were middle aged (mean age, 50.3 [SD, 9.0] years), and the majority were diagnosed with stage II breast cancer (53.8%). From baseline to 12 weeks, resting heart rate (mean [INCREMENT], +4.15 beats/min) and body mass index increased slightly (mean [INCREMENT], +0.47 kg/m 2 ). No clinically significant changes in HRQL or other psychosocial questionnaires, but social well-being decreased ( t 77 = 3.83, P = .000) slightly, and emotional well-being improved ( t 77 = −2.15, P = .034). Participants attended an average of 7.5 (SD, 6.5) classes; feedback about the program was positive, and no exercise-related injuries were reported. Conclusions: The BEAUTY program was feasible and effective in managing chemotherapy and radiation treatment–related declines in physical fitness and HRQL. Implications for Practice: This study supports the need to integrate exercise programming as part of treatment plans for breast cancer patients.